Interest of Grade X Students in Aquatic Learning at MA Multiteknik Asih Putera - Fajar Sidiq; Ani Pristiawati; Aep Rohendi (STKIP Pasundan Press, 2025)
This study aims to determine the level of interest of class X students at MA Multiteknik Asih Putera towards learning aquatic activities and the factors that influence it. Using a quantitative descriptive approach and survey method, data were collected through a closed questionnaire with 18 statements covering internal (attention, pleasure, and activity) and external (facilities and teacher's role) factors. The research sample was all class X students who participated in aquatic learning. The results of data analysis showed that in general student interest was in the moderate category (64.5%). Internal factors were rated as moderate by 61.3% of students, while external factors were also in the moderate category with a percentage of 62.9%. This finding shows that students' interest is quite good but not optimal, so improvement is needed in internal and external aspects to encourage higher learning interest in aquatic learning.